Pemanfaatan Media Sosial sebagai Sumber Belajar Alternatif dalam Pembelajaran Ekonomi SMA Panca Marga Lamongan - Muhammad Ulil Fadhli; Evi Aulia Rachma; Yayuk Chayatun Machsunah (Lembaga Pengembangan Kinerja Dosen, 2026)
The advancement of digital technology has triggered a transformation in the teaching and learning process, including in the teaching of Economics at the senior high school level. Social media, which initially served merely as a communication tool, is now utilized as an interactive and easily accessible alternative learning resource. This study aims to describe how social media is used in the Economics learning process at SMA Panca Marga Lamongan and to identify its benefits and challenges. The research employed a qualitative descriptive method with purposive sampling, involving one Economics teacher and eleventh-grade social science students. Data were collected through interviews, observations, and documentation, then processed and examined using the Miles, Huberman, and Saldaña analysis model. The findings show that social media platforms such as YouTube, Instagram, and TikTok enhance students’ understanding of economic concepts in a more contextual and visual manner, as well as foster learning independence and participation. However, challenges include difficulties in filtering credible information and the potential for distraction when usage is not well-controlled. Thus, social media can serve as an effective learning resource when supported by strong digital literacy, clear teacher guidance, and proper management of its use.